Sales Strategy Analysis Small Traders at Ampera Waterpark Cipanas - Akhmad Hidayat Nurul Akbar; Ade Yusuf (Nusantara Journal Of Management Business (NUMABI), 2023)
Study This aim For know 1) Profile trader small at Ampera Waterpark Cipanas , 2) How much good sales strategy trader small at Ampera Waterpark Cipanas . Method Research used _ in study This is method descriptive qualitative . Data used in study This namely primary and secondary data . Withdrawal technique sample in study This use total sampling or sampling saturated , that is all element population chosen as sample i.e. 15 traders small at Ampera Waterpark Cipanas . Analysis tools used _ is in a manner especially qualitative _ formerly tested validity and reliability the data . Research results show that : 1) Profile trader small sell product goods and services , 2) Sales strategy trader small at Ampera Waterpark Cipanas is very good , 3) Research results showing results recapitulation about indicator strategy Sales , got a total score of 642 is on point 630 – 750 is classified as very good and has score highest in statement number 4 and number 7 with score 69. Meanwhile very low value contained in the statement number 5 with score 60. In whole based on results on that sales strategy trader small in Ampera Waterpark Cipanas on the very good classification .